1998
DOI: 10.1136/jech.52.7.459
|View full text |Cite
|
Sign up to set email alerts
|

Costs, effects, and savings of screening for cystic fibrosis gene carriers

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
1
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 49 publications
0
39
1
1
Order By: Relevance
“…A systematic review of published economic evaluations of NBS (reported in Chapter 6) identified five studies that included a cost associated with information provision related to NBS. [119][120][121][122][123] In the two identified studies relevant to the UK setting, 119,120 an incremental cost of providing information, based on the additional time that it would take a midwife to explain the additional tests being evaluated, was used (£0.30 119 and £0.40 120 ). Pandor et al 119 provided little information on how the cost they used was derived, but did refer to being informed by a consultation with a midwife.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A systematic review of published economic evaluations of NBS (reported in Chapter 6) identified five studies that included a cost associated with information provision related to NBS. [119][120][121][122][123] In the two identified studies relevant to the UK setting, 119,120 an incremental cost of providing information, based on the additional time that it would take a midwife to explain the additional tests being evaluated, was used (£0.30 119 and £0.40 120 ). Pandor et al 119 provided little information on how the cost they used was derived, but did refer to being informed by a consultation with a midwife.…”
Section: Discussionmentioning
confidence: 99%
“…In a study carried out in Australia, Geelhoed et al 121 used a similar method, multiplying the salary cost for a midwife by the amount of time spent providing information. Wildhagen et al 122 estimated the cost of providing information about neonatal CF carrier screening by taking a value from a previous study 124 and scaling it by a factor of 60%. This study used a top-down approach that provided little information about how individual items of resource use were valued.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations